الجودة الشاملة والحوكمة في التعليم العالي (الرؤية الاستراتيجية الحديثة) (Comprehensive Journal of Science, 2025)
Abstract: This paper aims to explore the relationship between Total Quality Management (TQM) and governance in higher education as two strategic approaches that contribute to enhancing universities’ efficiency and responsiveness to societal and labor market needs. The paper reviews the theoretical concepts of TQM and governance and highlights the intersections between them, drawing on recent Arabic and international literature. The findings indicate that integrating principles of good governance with the philosophy of TQM provides a comprehensive framework for improving university performance, enhancing transparency, accountability, and effectiveness. The paper recommends that Libya universities adopt a strategic model that combines quality assurance mechanisms with governance tools to achieve a balance between institutional autonomy and social responsibility Keywords: Total Quality Management, Governance, Higher Education, Strategy, Universities
Keywords: word; word; word; (not more than 7 words).